Ocean Painting - Doctor Ron Clavier:::Creator::::::::::::
This series of paintings was done to portray specific scenes of Steinbeck's writings. See also numbers 1-559, 1-601, 1-246, 1-363, 1-596. Digital copy only. No hard copy.